Social asymmetries: clues to understand the spread of islamist jihadism in Cabo Delgado - Feijó, Friedrich-Ebert-Stiftung, Peace and Security Centre of Competence Sub-Saharan Africa, João (Friedrich-Ebert-Stiftung Peace and Security, 2020)
This article intends to reflect around the level of poverty and inequality existing among the various ethno-linguistic groups of the province, trying to gauge the extent to which they may be at the root of the current conflict. In this sense, 94 individuals were interviewed in the districts of Palma, Mocímboa da Praia, Macomia, Muidumbe and Montepuez (macuas, macondes, muânis and mácues), trying to understand what representations they build on the different ethno-linguistic groups in the province, in terms of access to business, employment and income, as well as State support. Throughout the text, an attempt is made to understand the socio-economic factors that can lead to the adherence (direct or indirect) of local populations to violent groups.
ISBN: 9782490093182 OCLC: 1199064112
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict / conflito; poverty / pobreza

Protecção social e poupança em 10 edicões dos desafios: que tipo de protecção social pode Moçambique desenvolver? - Siúta, Moisés S. (Desafios para Moçambique 2019, 2019)
Que tipo de protecção social poderá Moçambique desenvolver sem poupança interna e profundamente dependente da poupança externa? Esta é a questão principal que este artigo pretende discutir. A discussão é feita em dois sentidos: mostrar a importância da pesquisa dentro da qual a pergunta surgiu e mostrar a relevância da relação que a mesma estabelece entre a poupança e a protecção social. No primeiro sentido, a relevância da pesquisa é demostrada na abordagem das limitações e deficiências do sistema e formas de protecção social vigentes em Moçambique, destacando-se os elementos que podem contribuir para melhorar o sistema de protecção social moçambicano, abordados dentro do trabalho de pesquisa do IESE. Em geral, os resultados da pesquisa apontam como principal deficiência do sistema de protecção social em Moçambique a sua incapacidade de fornecer protecção digna aos cidadãos, que se socorrem das suas diversas formas (e.g.: demográfica ou financeira) e mecanismos de funcionamento (e.g.: familiar, comunitário, financeiro público e privado). No segundo sentido, a importância da pergunta principal do artigo é fundamentada teórica e empiricamente por meio da identificação das relações existentes entre a protecção social e a poupança e da forma como essas relações se manifestam no caso particular em Moçambique. Por exemplo, o artigo discute o quadro teórico de análise do papel da poupança no crescimento e desenvolvimento económico (figura 1) e a forma como este influencia e determina o tipo, as formas e a qualidade da protecção social que Moçambique pode oferecer aos seus cidadãos. Além do quadro teórico, recorrendo a dados empíricos dos países do mundo inteiro, busca-se enquadrar a economia e o sistema de protecção social moçambicano e estabelecer a relação entre o tipo, as formas e a qualidade da protecção social com o nível de poupança, crescimento e desenvolvimento económico.
Keywords: *tagged; Ethnographic Studies; G - Mozambique / Moçambique; L - portuguese / português; poverty / pobreza; social protection / proteção social; ⛔ No DOI found

“Our Lives Mean Nothing” - The Human Cost of Chinese Mining in Nagonha, Mozambique - Amnesty International (Amnesty International, 2018)
This report examines Haiyu’s conduct including what the company did or failed to do in acquiring the right to land for use of mining activity in Nagonha, what it did or failed to do in its operations in Nagonha, and what it did or failed to do in response to the villagers’ demand for compensation and resettlement following the flood. The report looks specifically at the breach of the right to adequate housing and decent living standards ensuing from Haiyu’s destruction of the wetland, and the related destruction of one-fifth of the village by the freak flood. The report also examines the Mozambican Government’s failure to protect, promote and fulfil the right to adequate housing and living standards in the village of Nagonha.
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; natural resources - mining / recursos naturais - mineração; poverty / pobreza

Strong but not Broadly Shared Growth. Mozambique Poverty Assessment - World Bank (World Bank, 2018)
Mozambique has recorded strong growth, but many low-income households are missing out on the benefits and policy options to make rowth more inclusive in Mozambique
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; poverty / pobreza

Social Protection in Mozambique: A new imperative? - Waterhouse, Dr Rachel; Lauriciano, Gil (2009)
Even before the impact of a global economic crisis kicks in, there is renewed thinking in Mozambique about a wider role for the state in social protection. Proponents are still struggling to convince others of the economic and social value of a broader investment in social protection. This is against the backdrop of institutional resistance borne of Mozambique’s political and economic history. The government attitude to social protection has been influenced by colonial experience of an extractive rather than protective state and the legacy of post-Independence events and processes. After Independence in 1975, initial social service expansion was heavily undermined by war-time destruction and economic collapse in the 1980s. Post war, the Government’s top priorities were to re-establish security and rebuild infrastructure. However, political and economic liberalisation in the 1990s saw tight caps on state spending. Poverty was so widespread and deep that there seemed to be little scope for special consideration of the ‘poorest of the poor’... except for ad hoc initiatives, such as the food subsidy programme for the poor and unable to work. In the last 15 years, Mozambique has experienced impressive economic growth and poverty reduction. Nonetheless Mozambique continues to rank amongst the world’s poorest countries. Government is becoming more aware of chronic poverty and that large population groups are currently unable to escape the poverty trap. This raises debate about what can be done ... and promotes renewed thinking on social protection. There are still many obstacles to a coherent and comprehensive approach to social protection. These include: analytical limitations around the causes, consequences and extent of vulnerability as well as the potential social and economic benefits of social protection; institutional barriers; budgetary limitations; and perceived political risk. However, there is also a growing acceptance of the relevance and importance of social protection to reduce vulnerability, build resilience and contribute to poverty reduction. These issues need to be addressed at policy and practical level, if Mozambique is to effectively address the growing challenge of chronic poverty.
Keywords: *tagged; Ethnographic Studies; G - Mozambique / Moçambique; L - english / inglês; poverty / pobreza; social protection / proteção social

Adverse incorporation, social exclusion and chronic poverty - Hickey, Samuel; Andries du Toit (Institute for Development Policy and Management, School of Environment and Development, University of Manchester, 2007)
There are a number of compelling reasons to focus on the ways in which the processes and relations of adverse incorporation and social exclusion (AISE) underpin chronic poverty. In particular, AISE research draws attention to the causal processes that lead poverty to persist, and to the politics and political economy of these processes and associated relationships over time. Specific dimensions of AISE are explored in relation to chronic poverty – namely political, economic, socio-cultural and spatial – and are found to relate closely to long-term historical processes, particularly concerning the nature and forms of capitalism, different stages and types of state formation, and institutionalised patterns of social norms and attitudes. However, it is also stressed that much of the promise of AISE research lies in its capacity to cross analytical boundaries and capture the multi-dimensional and interlocking character of long-term deprivation. This analysis suggests a number of fruitful areas for research, most of which are currently under-explored in poverty research. In methodological terms, there are benefits to adopting integrated qualitative-quantitative approaches when investigating AISE, although it is argued that (a) the relational nature of AISE and the limitations of quantitative data may dictate that qualitative work should take priority here and (b) that more historical and theoretically oriented forms of research are particularly appropriate in studying AISE. To think about challenging AISE involves shifting the frame from policy to politics and from specific anti-poverty interventions to longer-term development strategies, particularly in terms of industrialisation and labour market restructuring, moves towards developmental states and supporting shifts from clientelism to citizenship. However, a range of more immediate development policy interventions may also be able to make headway in challenging the forms of AISE that perpetuate poverty.
OCLC: 317916213
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; poverty / pobreza; social inclusion & exclusion / inclusão e exclusão social

Impacto da Economia Informal na Protecção Social, Pobreza e Exclusão: A Dimensão Oculta da Informalidade em Moçambique - Francisco, António A da Silva; Paulo, Margarida (CRUZEIRO DO SUL – INSTITUTO DE INVESTIGAÇÃO PARA O DESENVOLVIMENTO JOSÉ NEGRÃO, 2006)
O trabalho anunciado no título desta monografia analisa a economia informal e a protecção social, bem como os seus impactos, directos e indirectos, no desenvolvimento económico e humano, na pobreza e na exclusão social em Moçambique. A resposta e os resultados que a monografia encontrou para as questões principais de pesquisa revelaram-se, de algum modo, surpreendentes, tanto para os promotores do estudo como para os organizadores e os próprios autores. A surpresa não é por causa da revelação que a informalidade domina a sociedade moçambicana. Afinal de contas, os números aqui reunidos, segundo os quais a economia informal domina 90% da economia de Moçambique, apenas confirmam o que as pessoas sentem e vivem na sua vida quotidiana. As surpresas reveladas neste trabalho têm a ver com os mitos e falácias em que as pesquisas sobre economia informal em Moçambique têm acreditado. Do ponto de vista analítico e prático, a presente monografia levanta um duplo desafio, um relacionado directamente com a economia informal e o outro com a protecção social.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; Social Protection PEA; economic development / desenvolvimento económico; employment / emprego; informality / informalidade; poverty / pobreza; social protection / proteção social

Islamic Radicalization in Northern Mozambique: The Case of Mocímboa da Praia - Habibe, Saide; Forquilha, Salvador; Pereira, João (Instituto de Estudos Sociais e Económicos (IESE))
Este artigo analisa o fenómeno da radicalização islâmica no Norte de Moçambique, explorando a complexidade das dinâmicas não só na origem do grupo dos Al-Shabaab como também na estrutura do próprio conflito e violência em Cabo Delgado. Os autores consideram que o fenómeno exige uma pesquisa multidisciplinar aprofundada que tome em conta uma multiplicidade de factores de ordem histórica, social, política, económica e religiosa. Acesso à versão inglesa aqui. —– This research report is a first attempt to address the phenomenon in order to understand the complexity of the dynamics not only in the origin of the Al-Shabaab group but also in the structure of the conflict and violence in Cabo Delgado. Almost two years after the first attack on Mocímboa da Praia (5 October 2017), the phenomenon has been the subject of multiple interpretations, from the (at least public) Mozambican government’s preferred thesis of a conspiracy driven by external forces opposed to Mozambique’s development, through the land conflict against the backdrop of the area’s natural resources thesis, to the sect (Morier-Genoud, 2019) and jihadism theses, in the context of the growing dynamics of violent extremism in the countries of the region i.e. Tanzania, Kenya and the Great Lakes region. While highlighting this last thesis (jihadism), our exploratory research has shown that the phenomenon is complex and requires profound multidisciplinary research that takes into account a multiplicity of historical, social, political, economic and religious factors. This is why, rather than draw conclusions, this report ends with a series of questions: • Why is Mocímboa da Praia the epicentre of the phenomenon? • How does the Mozambican state deal with the proliferation of religious institutions in the country? • What are the implications of the Islamic radicalization phenomenon for investments in the country’s northern region? To what extent can these investments heighten or reduce local cleavages and contribute to Islamic radicalization phenomenon? • To what extent does the Islamic radicalization phenomenon affect current efforts to stabilize the country politically and economically? • To what extent can regional dynamics (Tanzania, Kenya, Great Lakes region) influence the evolution of the phenomenon in Mozambique? • What kind of policies (including security) does the country need to address the phenomenon? • What lessons does the phenomenon bring to the state-building process in Mozambique? These questions feed into the ongoing research program at the Institute for Social and Economic Studies (IESE) since early 2019, involving researchers from IESE and other research centres, entitled “State, Violence and Development Challenges in Cabo Delgado”.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Mocímboa da Praia; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; poverty / pobreza; youth / juventude